Why? : explaining the Holocaust - Hayes, Peter 1946- (W.W. Norton & Company, 2017)
Why another book on the Holocaust? -- Targets: why the Jews? -- Attackers: why the Germans? -- Escalation: why murder? -- Annihilation: why this swift and sweeping? -- Victims: why didn't more Jews fight back more often? -- Homelands: why did survival rates diverge? -- Onlookers: why such limited help from outside? -- Aftermath: what legacies, what lessons?